Ascendentne živčne proge - Meh, Duška (Medicinski razgledi, 1996)
Our activites are controlled by nerve tracts, i.e. groups of nerve fibres with the common origin, course and destination. Afferent nerve pathways conveying information to the central nervous system are presented. The exact role of some of them has not yet been definitely determined. Knowledge of the function and anatomy of nerve tracts, enables us to localise various nervous defects.
Keywords: medicina; medicine; ascendentne živčne proge